Identification of 2 novel homozygous mutations in the methylmalonyl-CoA mutase gene in Saudi patients - Mohamed, Sarar (Saudi Med J, 2015)
The aim of this report is to analyze the clinical features, and mutations of the methylmalonyl CoA mutase (MUT) gene in 2 patients with methylmalonic aciduria (MMA) attending King Saud University Medical City, Riyadh, Saudi Arabia in January 2014. The infants aged 6 days (patient 1) and 3 months (patient 2) with sepsis-like picture, metabolic acidosis, and hyperammonemia were presented. Investigations revealed high propionylcarnitine (C3), elevated urinary methylmalonic acids, 3-hydroxypropionic acids and methylcitrate, consistent with MMA. Sanger-sequencing detected a homozygous novel mutation (c.329A>G; p.Y110C) in the MUT gene in patient 1 and a heterozygous in parents. This mutation is predicted to have a damaging effect on the protein structure and function. In patient 2, we detected a novel homozygous nonsense mutation (c.2200C>T; p.Q734X) and a heterozygous in parents. This mutation leads to a premature stop-codon at codon 734 of the MUT gene. We identified 2 novel mutations in the MUT gene causing isolated MMA.